The Flag of Tibet: A Vexillological Reading (Bodhi Path, 2025)
This paper undertakes a vexillological reading of the Tibetan national flag, examining its historical evolution, symbolic imagery, and significance in articulating Tibetan identity and resistance. While much scholarly attention has been devoted to Tibetan Buddhist prayer flags, the national flag—popularly known as the Snow Lion Flag—remains under-explored within vexillological discourse. Drawing on semiotics, cultural history, and political theory, the paper analyses the flag’s imagery, including the snow lion, mountain, sun, and the debated yin-yang motif, to uncover its embedded narratives of sovereignty, spirituality, and collective memory. It traces the flag’s transformation from a military standard under the Thirteenth Dalai Lama to its role as a banned yet potent symbol of resistance in contemporary Tibet and exile communities. Ultimately, the paper argues that the Tibetan flag functions not merely as a political emblem, but as a dynamic, transhistorical artefact embodying national aspiration, cultural continuity, and decolonial identity in the face of occupation.
Keywords: Tibet, vexillology, national flag, symbolism, snow lion, exile, identity, resistance, semiotics, decoloniality